Interactive Modules Containing Problem Based Learning with Socioscientific Issues on The Water Cycle Material - Riska Septianita; Erni Suharini; Arif Widiyatmoko; Putut Marwoto; Sungkowo Edy Mulyono (Jurnal Penelitian Pendidikan IPA, 2023)
The learning innovation developed is combining learning modules with the use of mobile phones so that learning is interactive and meaningful. The preparation of the module uses the PBL stages with the content of socioscientific issues according to what happens in everyday life so that it is expected to train one of the 21st century skills is critical thinking skills and support digitization of education. This study aims to develop an interactive module containing problem based learning with socioscientific issues on the water cycle material and to determine the content and construct validity of the developed learning modules. The method used in development research was adapted from the RnD method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique was in the form of a validation questionnaire for material experts, linguists, and media experts. From the results of data validation and analysis, a percentage of 95.55% was obtained for content validation and a percentage of 97,52% for construct validation, both of which were classified as very valid. From these results it can be concluded that the interactive module containing Problem Based Learning with socioscientific issues in the water cycle material is feasible to use in terms of validity aspects